2011
DOI: 10.1111/j.2044-8341.2011.02028.x
|View full text |Cite
|
Sign up to set email alerts
|

Adult attachment insecurities are associated with obsessive compulsive disorder

Abstract: Addressing attachment anxiety in individuals presenting with OCD may be important for enhancing therapeutic outcomes. However, findings are based on cross-sectional data that preclude conclusions relating to causal influence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 76 publications
4
31
0
2
Order By: Relevance
“…Attachment insecurities have been suggested to play an important role in the maintenance and development of OCD (Doron & Kyrios, 2005;Doron, Moulding, Kyrios, Nedeljkovic, Mikulincer, & Sar-El, 2012) and relationship-related OC symptoms (Doron et al, in press, 2012). More specifically, attachment insecurities were suggested to exacerbate sensitivity to intrusive thoughts by disrupting functional coping with experiences that challenge highly important self-domains (Doron, Moulding, Kyrios, Nedeljkovic, & Mikulincer, 2009).…”
Section: Discussionmentioning
confidence: 97%
“…Attachment insecurities have been suggested to play an important role in the maintenance and development of OCD (Doron & Kyrios, 2005;Doron, Moulding, Kyrios, Nedeljkovic, Mikulincer, & Sar-El, 2012) and relationship-related OC symptoms (Doron et al, in press, 2012). More specifically, attachment insecurities were suggested to exacerbate sensitivity to intrusive thoughts by disrupting functional coping with experiences that challenge highly important self-domains (Doron, Moulding, Kyrios, Nedeljkovic, & Mikulincer, 2009).…”
Section: Discussionmentioning
confidence: 97%
“…In another study on a mixed psychiatric sample, the patients with panic disorder and obsessive-compulsive disorder scored higher on attachment-related anxiety as compared with healthy individuals [31]. Recently, attachment anxiety was found to be significantly higher in individuals with obsessive-compulsive disorder than in healthy controls, even when controlling for depression [18]. Consistently with theoretical expectations [7] and with these previous studies, we found significantly higher levels of attachment-related anxiety among patients with anxiety disorders as compared with both healthy controls and patients with drug-resistant epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…All these studies reported an association between attachment insecurity and anxiety [15-18]. Negative attachment-related experiences such as unfavorable parental attitudes were also found to be associated with disorders such as panic disorder [19, 20] and generalized anxiety disorder [21].…”
Section: Introductionmentioning
confidence: 99%
“…Doron and Kyrios (2005;Doron, Moulding, Kyrios, & Nedeljkovic, 2008) argued that highly valued self-domains where the person lacks confidence may contribute to sensitivity to obsessions. Obsessional thoughts that threaten these "sensitive" self domains are more likely to become the object of appraisal, preoccupation and anxiety Doron, Kyrios, Moulding, Nedeljkovic, et al, 2007;Doron et al, 2008), particularly when coupled with poor emotional regulation such as in the form of dysfunctional attachment systems (Doron, Moulding, Kyrios, Nedeljkovic, & Mikulincer, 2009;Doron, Moulding, et al, 2012;Doron, Sar-El, & Mikulincer, 2012). Experimental studies also show that threat to specific self-domains (e.g., morality or relationships) may result in an increase in thematically-related (e.g., contamination and relationship-centred) obsessive-compulsive behavioural tendencies (i.e., Doron, Sar-El, et al, 2012;Doron, Szepsenwol, Karp, & Gal, 2013).…”
Section: Obsessional Doubtmentioning
confidence: 99%